2013
DOI: 10.1128/ec.00027-13
|View full text |Cite
|
Sign up to set email alerts
|

A Bacterial Phosphatase-Like Enzyme of the Malaria Parasite Plasmodium falciparum Possesses Tyrosine Phosphatase Activity and Is Implicated in the Regulation of Band 3 Dynamics during Parasite Invasion

Abstract: f Eukaryotic parasites of the genus Plasmodium cause malaria by invading and developing within host erythrocytes. Here, we demonstrate that PfShelph2, a gene product of Plasmodium falciparum that belongs to the Shewanella-like phosphatase (Shelph) subfamily, selectively hydrolyzes phosphotyrosine, as shown for other previously studied Shelph family members. In the extracellular merozoite stage, PfShelph2 localizes to vesicles that appear to be distinct from those of rhoptry, dense granule, or microneme organel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 40 publications
5
28
0
Order By: Relevance
“…Studies of apicomplexan SLPs have been limited to P. falciparum where PfSLP2 was shown to possess tyrosine phosphatase activities like other SLPs and to localize to the apical end of invasive merozoites within some vesicles distinct from dense granule, rhoptry and micronemes (Fernandez-Pol et al, 2013). Prior to parasite invasion, the interaction between Band3, an erythrocyte membrane protein, and the erythrocyte cytoskeleton is disrupted by the phosphorylation of Band3 to facilitate invasion (Fernandez-Pol et al, 2013). It has been proposed that, after the completion of parasite invasion, secreted PfSLP2 dephosphorylates Band3 and restores the interaction between erythrocyte Band3 and cytoskeleton (Fernandez-Pol et al, 2013).…”
Section: Ppkl Efpp and Slpmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of apicomplexan SLPs have been limited to P. falciparum where PfSLP2 was shown to possess tyrosine phosphatase activities like other SLPs and to localize to the apical end of invasive merozoites within some vesicles distinct from dense granule, rhoptry and micronemes (Fernandez-Pol et al, 2013). Prior to parasite invasion, the interaction between Band3, an erythrocyte membrane protein, and the erythrocyte cytoskeleton is disrupted by the phosphorylation of Band3 to facilitate invasion (Fernandez-Pol et al, 2013). It has been proposed that, after the completion of parasite invasion, secreted PfSLP2 dephosphorylates Band3 and restores the interaction between erythrocyte Band3 and cytoskeleton (Fernandez-Pol et al, 2013).…”
Section: Ppkl Efpp and Slpmentioning
confidence: 99%
“…Prior to parasite invasion, the interaction between Band3, an erythrocyte membrane protein, and the erythrocyte cytoskeleton is disrupted by the phosphorylation of Band3 to facilitate invasion (Fernandez-Pol et al, 2013). It has been proposed that, after the completion of parasite invasion, secreted PfSLP2 dephosphorylates Band3 and restores the interaction between erythrocyte Band3 and cytoskeleton (Fernandez-Pol et al, 2013). In a separate study PfSLP1 was shown to be expressed in all stages of parasite life cycle, and its deletion affected microneme formation, and ookinete development and resulted in complete inhibition of oocyst formation (Patzewitz et al, 2013).…”
Section: Ppkl Efpp and Slpmentioning
confidence: 99%
“…Mammalian Plasmodium development process initiate species proceeds via asexual exoerythrocytic proliferation and intraerythrocytic multiplication that existing in mammalian liver hepatocytes and erythrocytes, respectively, whereas sporogony and sexual development take place in the mosquito [6]. Plasmodium is related to the phylum Apicomplexa, which is characterized and indicated by the distinct apical organelles presence consisting of micronemes, dense granules, and rhoptries that are used by the parasite for gliding motility and host invasion [7] Of the three invasive stages (sporozoites, merozoites, and ookinetes), the ookinetes uniquely lacks rhoptries and dense granules [8]. There are two nonconventional PPs, one of them is containing an N-terminal β-propeller formed by kelchlike motifs and the other a Shewanella-like PP (SHLP1), are required during ookinetes-to-oocyst transition and subsequent transmission of the malaria through P. berghei [9].…”
Section: Shewanella-like Protein Phosphatase (Shlp)mentioning
confidence: 99%
“…Homology Modeling of all 4 proteins was done and modeled was obtained using Schrodinger Software Suite. The modeled structures and their respective Ramachandran Plot are specified in the figures (1)(2)(3)(4)(5)(6)(7)(8). Two variants of SHLP protein (SHLP1 and SHLP2) was found in four different species of plasmodium (Plasmodium sp., Plasmodium ovale, Plasmodium reichenowi, and Plasmodium berghei) retrieved through UniProt database.…”
Section: ) Homology Modeling Using Schrödinger Softwarementioning
confidence: 99%
“…Based on its sequence, it is also a Ser/Thr-protein phosphatase (16), yet it displays dual specificity activity toward pSer, pThr, and pTyr peptides. Previous work on the Plasmodium equivalents of plant SLP1 and SLP2 (SHLP1 and -2) (31,37) indicates that, like AtRLPH2, they are resistant to okadaic acid and microcystin. Moreover, like the cold-active phosphatase originally described in Shewanella (38), SHLP2 has been shown to preferentially dephosphorylate phospho-tyrosine.…”
mentioning
confidence: 99%